Ecotoxicological effects of untreated pig manure from diets with or without growth-promoting supplements on Eisenia andrei in subtropical soils - Maccari A.P.* (2022)
© 2022, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.This study aimed to evaluate the effects of untreated pig manure from diets incorporating growth-promoting supplements (antibiotics and Zn oxide) on the survival and reproduction of Eisenia andrei earthworms. The tested manures were obtained from four different groups of pigs fed with four different diets: CS, a diet based on corn and soymeal; TR, a diet based on corn, soymeal, and ground wheat (15%); CSa, a diet based on corn and soymeal + 100 ppm of doxycycline + 50 ppm of colistin + 2500 ppm of Zn oxide; and TRa, a diet based on corn, soymeal, and ground wheat (15%) + 100 ppm of doxycycline + 50 ppm of colistin + 2500 ppm of Zn oxide. The study used two soils representative of the Southern region of Brazil (Oxisol and Entisol). In general, there were no significant differences between the different manures tested in each soil. However, there were differences in the toxicity manure on E. andrei between the soils, and the magnitude of this effect was dependent on the applied dose. In Oxisol, LC50 values were higher than 80 m3 ha−1, and EC50 varied from 9 to 27 m3 ha−1. In Entisol, the LC50 values were below the lowest dose tested (< 25 m3 ha−1), and EC50 remained around 5 m3 ha−1. It may be possible that the effects observed were attributed to an excess of nitrogen, copper, and zinc, promoted by the addition of the untreated manure and how these factors interacted with soil type.